Proyeksi Produksi Migas Indonesia Sampai Dengan Tahun 2045 - Mohammad Edgar Dewanto (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2023)
This study aims to determine how the influence of production on imports. The analytical tools used are trend analysis and simple linear regression analysis using time series data. The results of the study show that the projected oil and gas production fluctuates and tends to decrease every year, and the results of the production research whether it affects imports, the result is that the amount of production does affect the amount of imports and has a positive effect.